Decentralisation, School-Based Management, and Quality
XXVI, 238 p.
Keywords: The relationship between government, education reform and student outcomes is an ambivalent and often problematic one. Focusing on the interplay between decentralization, globalization, and education reforms, this book draws on recent studies to explore the conceptual frameworks and methodological approaches that can be applied to research covering the state, globalization, equality, and education. It lays bare the neo-liberal ideological imperatives of education and policy reforms, and illustrates the way the relationship between the state and education policy affects current models and trends in education reforms and schooling globally. The chapters critically analyze the dominant discourses about decentralization and comparative education and examine the current resurgence of neo-liberal ideological models in education, both newly constructed and re-invented. To ensure as broad a perspective on the issues as possible, the authors employ a raft of diverse paradigms in comparative education research, ranging from critical theory to globalization. This in-depth exploration of globalization, ideology and democracy in education examines both the reasons for and outcomes of education reforms, decentralization, policy change and transformation. In doing so, it seeks to provide a more informed critique on Western-driven models of accountability, quality and school effectiveness. It is the eighth in the 12-volume book series Globalization, Comparative Education and Policy Research, which presents scholarly research on major discourses in comparative education research with reference to decentralization and school-based management. The series provides an accessible, practical yet scholarly source of information about international issues in the field of globalization and comparative education.